Animation Video Based on Balinese Ethnomathematics on Flat Buildings Material - Desak Putu Yuniari; I Made Suarjana; I Nyoman Laba Jayanta (Jurnal Ilmiah Sekolah Dasar, 2025)
The problem of this research departs from the low critical thinking and metacognitive skills of students in learning mathematics, especially in flat building materials. This is caused by learning approaches that tend to be conventional and lack of linking mathematical concepts with the context of everyday life, so that students have difficulty understanding the material in depth. This study aims to create an animation video based on Balinese ethnomathematics that is valid, practical, and effective to be used to improve critical thinking skills and metacognitive abilities of grade V elementary school students on flat area material. The type of research used is quantitative research. The subjects in this study were 20 fifth grade students. The data collection method used questionnaires and descriptive tests. Data from pre-test and post-test results were analyzed using t test with correlated samples to determine the effectiveness of the product. The main results of this study indicate that the Balinese ethnomathematics-based animated video on flat building material significantly contributes to improving the critical thinking and metacognitive skills of grade V students. The effectiveness test showed a significant increase in students' critical thinking skills, as seen from their ability to analyze, evaluate, and solve problems related to the material. The implication of this research is to illustrate that developing ethnomathematics-based animated videos in the implementation of mathematics learning can train students' critical thinking skills and metacognitive abilities, especially on the material of flat areas.